Molecular Mechanisms of PALB2 Function and Its Role in Breast Cancer Management - Wu, Shijie; Zhou, Jiaojiao; Zhang, Kun; Chen, Huihui; Luo, Meng; Lu, Yuexin; Sun, Yuting; Chen, Yiding (Frontiers in Oncology, 2020)
Partner and localizer of BRCA2 (PALB2) is vital for homologous recombination (HR) repair in response to DNA double-strand breaks (DSBs). PALB2 functions as a tumor suppressor and participates in the maintenance of genome integrity. In this review, we summarize the current knowledge of the biological roles of the multifaceted PALB2 protein and of its regulation. Moreover, we describe the link between PALB2 pathogenic variants (PVs) and breast cancer predisposition, aggressive clinicopathological features, and adverse clinical prognosis. We also refer to both the opportunities and challenges that the identification of PALB2 PVs provides in breast cancer genetic counseling and precision medicine.